EFFECT OF SEX AND NUMBER OF DEVELOPING FOETUS ON PHYSIOLOGICAL RESPONSE IN CROSSBRED DOES (Indian Journal of Animal Production and Management, 2015)
Fifteen, 19-24 months old, farm born primiparous crossbred goats were randomly selected to study the effect of foetal sex and number on physiological responses and body weight changes during last three months of pregnancy. The pulse rate was significantly (P
Keywords: Doe; foetus; rectal temperature; Pulse rate; respiration rate; body weight